Remoteness and Real Exchange Rate Volatility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines the impact of trade costs on real exchange rate volatility. The channel is examined by constructing a two-country Ricardian model of trade, based on the work of Dornbusch, Fischer, and Samuelson (1977), which shows that higher trade costs result in a larger nontradable sector. This, in turn, leads to higher real exchange rate volatility. We provide empirical evidence supporting the channel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet